Review of Literature Studies Regarding the Implementation of Business Process Management - Titi Puspitasari; Jeni Susyanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research was carried out with a literature review study to find out findings regarding the development of Business Process Management (BPM) and its implementation in business and various fields in the era of increasingly rapid digitalization and globalization. This research was conducted to complement and expand literature sources regarding BPM from previous research. The method used is a study literature review of 30 internationally indexed articles from Google Scholar from 2020-2024. The results of the literature review study analysis explain BPM as a foundation for business processes in various fields, especially digital transformation and digital innovation. BPM also contributes to BCT, CBP, quality management, IT, AI, IoT, PPM, ABPMS and others. However, it does not have a significant effect on measuring financial risk in company performance so that it contributes to the literature and development of this topic for researchers and practitioners in the future.